2023
DOI: 10.1021/acs.est.3c02495
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Based Nanomaterials and Plant Growth Promoting Rhizobacteria Synergistically Degrade Polychlorinated Biphenyls by Producing Extracellular Reactive Oxygen Species

Abstract: Plant growth promoting rhizobacteria (PGPR) produce extracellular reactive oxygen species (ROS) to protect plants from external stresses. Fe-based nanomaterials can potentially interact with PGPR and synergistically degrade organic pollutants, yet they have received no study. Here, we studied how the interaction between a typical PGPR (Pseudomonas chlororaphis, JD37) and Fe-based nanomaterials facilitated the degradation of 2,4,4′-trichlorobiphenyl (PCB28), by comparing the zerovalent iron of 20 nm (nZVI20), 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…in the cotreatment (FJ) was statistically and significantly higher than that in the control group ( p = 0.025), indicating the colonization of JD37 in alfalfa rhizosphere (Figure S9). Previous studies have reported that Pseudomonas can directly mediate the redox transformation of iron by secreting metabolites with acidic and reducing properties. In this study, an indirect mechanism was proposed that Pseudomonas chlororaphis JD37 promoted the transformation of Fe-based NMs by promoting the secretion of acidic and reducing metabolites from plant roots and participating in the rhizosphere Fenton reaction.…”
Section: Resultsmentioning
confidence: 87%
“…in the cotreatment (FJ) was statistically and significantly higher than that in the control group ( p = 0.025), indicating the colonization of JD37 in alfalfa rhizosphere (Figure S9). Previous studies have reported that Pseudomonas can directly mediate the redox transformation of iron by secreting metabolites with acidic and reducing properties. In this study, an indirect mechanism was proposed that Pseudomonas chlororaphis JD37 promoted the transformation of Fe-based NMs by promoting the secretion of acidic and reducing metabolites from plant roots and participating in the rhizosphere Fenton reaction.…”
Section: Resultsmentioning
confidence: 87%